A performance analysis of the spray-type packed bed thermal energy storage for concentrating solar power generation. (July 2022) - Bai, Yakai; Wang, Liang; Lin, Lin; Lin, Xipeng; Peng, Long; Chen, Haisheng
Abstract: The concept of spray-type packed bed thermal energy storage (medium and high temperature thermal energy storage, from 200 °C to 350 °C, Alumina pellets+T66 fluid) has been proposed in our previous investigation. Its low-cost and high-efficiency shows its promising application prospect. Further investigation of the new concept is carried out both numerically and experimentally in this paper. First, the "charging-standby-discharging" cycle of a pilot spray-type packed bed is investigated experimentally. Second, the dynamic liquid holdup of the spray-type packed bed is correlated with the experiment data and is applied to build the mass balance equations. Based on the energy balance equations and mass balance equations, a three-phase one-dimensional transient model for the spray-type packed bed is established. Results from the experiment confirms the correctness of the numerical model. Based on the model, the liquid holdup of the packed bed during the "charging-standby-discharging" cycle is studied. At last, sensitivity analysis was carried out to study the influence of the parameters of the "charging-standby-discharging" process on the thermal performance of the spray-type packed bed. Values of these parameters can be found to achieve the best thermal performance of a spray-type packed bed.